Titanium Pyrophosphate for Removal of Trivalent Heavy Metals and Actinides Simulated by Retention of Europium. (12th July 2017) - Ortiz-Oliveros, Huemantzin Balan; Flores-Espinosa, Rosa María; Ordoñez-Regil, Eduardo; Fernández-Valverde, Suilma Marisela
Abstract : This work addresses the synthesis of titanium pyrophosphate, as well as the characterization and evaluation of the sorption process of europium, for removal of trivalent heavy metals and actinides simulate. The evaluation of the surface properties of titanium pyrophosphate was carried out determining the surface roughness and surface acidity constants. The values obtained from the determination of the surface roughness of the synthesized solid indicate that the surface of the material presents itself as slightly smooth. The FITEQL program was used to fit the experimental titration curves to obtain the surface acidity constants:log ⁡ K + = 3.59 ± 0.06 andlog ⁡ K - = - 3.90 ± 0.05 . The results of sorption kinetics evidenced that the pseudo-order model explains the retention process of europium, in which the initial sorption velocity was 8.3 × 10 −4  mg g −1  min −1 and kinetic constant was 1.8 × 10 −3  g mg min −1 . The maximum sorption capacity was 0.6 mg g −1 . The results obtained from sorption edge showed the existence of two bidentate complexes on the surface.